Przyjmowanie orędzia wiary na przykładzie afrykańskich ludów Tanzanii - Balwierz, Marian (Śląskie Studia Historyczno-Teologiczne, 1984)
The indigenous connection between the religion and the life remains a stable element of all the changes, which occur in the modern Africa. Therefore, the religious values occupy permanently the same position in the African life in spite of its all modern transformations. This fact have to be taken into account during the process of looking for the new African models of the man, culture and civilization. In these circumstances, the African and some other people ask about the usefulness of the different religions for the creation of the new African style of life. Such a question regarding the Christianity was also put by some writers. An afirmative answer on it is grouded on two facts. The great internal capability of the Christianity for the cultural adaptation is one of them. The very existence of the incarnation of the Christianity into the real life of some modern African societies is the other one. The Catholicism and the life of the Tanzanian society are exemplary taken here as a ground for the fundamental reflexion regarding those two facts. The permanent missionary activity of the Christians and the world-wide range of this religion are some exceptional events in the general phenomenon of the religious life of man. Likewise these two exceptional events testify that this religion possesses an unusual capability as well of an accommodation as of an absorbtion during its contact with the diffrent cultures and civilizations of the world. Both elements, namely the accommodation and the absorbtion, are the essential components of a new missionary method, which is called “an inculturation”. The Ecclesiology, which is grounded on the History of Salvation, forms the proper meaning of the Catholic absorbtion. In this framework, the missionary absorbtion is only a part of the Church's evangelization. This part of the evangelization realizes a process of an introduction of Jesus Christ and His Gospel into the new culture. Such an introduction of the first, essential Christian value serves above all for the true development of the evangelized reality. The dialogical and ecclesiastical nature of the comprehensive Catholic faith shapes its proper accommodation in the evangelized culture. The evangelizing Church have to enter upon a dialogue with the non Christian cultures and religions in this process. This Church cannot try to force some doctrines, ideologies or outlooks on life upon those cultures, because the real Catholic Truth is the Word of God which became a human being, i.e. Jesus Christ living in His Church now. Therefore, the evangelizers who work for the proper accommodation of the Catholic faith in some new culture, have to make only Jesus Christ to be a present reality in it. This is their care for the proper accommodation of the faith, which is a process almost identical with the missionary absorbtion in this background. The missionary absorbtion and the missionary accommodation are only two diffrent aspects of the one, evangelizing process. It is called “an inculturation” today. The most essential part of this inculturation is a meeting of Jesus Christ living in the Church with the evangelized culture. Some new culture is created during such a meeting. This process differs totally from an aculturation, because the new culture does not come into being here in a result of the contact of two or more cultures but in a result of the contrast of the evangelized culture with the person of Jesus Christ living in His Church. This person gives the whole newness to the inculturation, which belongs to the very nature of the present life of the missionary People of God. Apart from the theological reflection, some facts from the life of the evangelizing Church testify in favour of the presented truth. The reception of the evangelical message of the faith by the real society exposed to the missionary evangelization of the Church is one of them. Today this reception occurs for example in the life of the Tanzanian society. It involves four facts: the traditional religious experience of Tanzanians, the africanization of the Church's life, the coexistence of the Church with the State and the advantages granted by the existence of the post-Christian communities. These facts seen together suggest that the Tanzanian Christians are really working for the full, proper reception of the Catholic faith by the new culture which comes into being in this African country now. The traditional African religious values are the natural foundations for the development of the grace of the living faith among the people of Tanzania. However, these values are not a reality either for a conquest or for a rejection by the evangelizing Church, because they are offered to God by those people, who enter into the salvific dialogue with Him. Therefore, the Tanzanians have to incarnate permanently Jesus Christ who is evangelized to them, into their own traditional religious experience. The Catholic faith of them comes into existence only on this way. The africanization of the Church's life in Tanzania is the most explicit sign of the development of this Catholic faith of the Tanzanian Christians. The evangelization realized on the level of the parish life works first of all for this africanization in the local Church of that African country. The liturgy, the catechesis and the mutual relations between the people become more indigenous in a result of this process. At the same time, the new, more Christian culture grows in the real life of the Tanzanian society. What is more, this effort of the evangelizing Church meets congenial efforts of the Goverment of that society. Therefore, the mutual relations between the Church and the State are the first sign of the true africanization of the church's life in Tanzania. The Tanzanian form of goverment is bazed on the local tradition of the common life in this part of Africa and therefore, the care for the full development of the local man is the first aim for the activity of the civil authorities of this country. However, the activity of the evangelizing Church aims also to the full development of man. This identity of tasks gives grounds for the wide mutual co-operation of the Church and the State in Tanzania. Such a co-working is very important for the proper inculturation, because it does not involve only the leaders but also the wide masses of the People of God in the africanization of the Church's life. Such an involvement determines the reality of the true inculturation. The religious syncretism is the worst danger for the evangelization. It is a matter of fact, that some syncretical post-Christian religious movements exist as well in Tanzania as in the whole of Africa. They are not of course, the true Catholic or African attempts of forming a very African Christianity, because they result from the sociological aculturation. However, the existence of those movements helps the inculturation as they can absorbe the local syncretical indications of some Tanzanians. These movements help also the evangelizing Church to know and to avoid some mistaces in her evangelization. An observation about the very important role of the Christianity in the process of forming the new African reality concludes this reflection as well in its more theological as in its more missiographical part. This importance flows from the one fact. The Christians do not offer some ideology but the living person during the evangelization performed by them. It is the person of Jesus Christ living in the Church now. A good realization of such an offer by all modern evangelizers depends on the usage of the method of inculturation by them today.